EFEKTIVITAS DIALISER PROSES ULANG (DPU) PADA PENDERITA GAGAL GINJAL KRONIK (HEMODIALISA) - Ratnawati, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
The cost of HD is a major constraint for HD therapy for patients with chronic renal failure undergoing HD. Oneway to reduce cost is to use a Re-Used Dialiser (DPU). The purpose of this study to determine how effective the use of DPU for those who have the chronic renal failure. The method used is to make observation of decreased levels of blood urea before and after use a new dialiser (DPU1), in 5th (DPU5) and 10th (DPU10). Then the data obtained will be analyzed using statistical descriptive and inference. The result can be concluded that there are differences in level blood urea before and after HD. The result are not significant at DPU1 and DPU5, but significant enough at DPU10.